DNA barcoding of intertidal barnacles as potential bioindicators of microplastic pollution in Seribu Islands and Jakarta Bay, Indonesia - MIFTAKHUL SEFTI RAUFANDA; ROMANUS EDY PRABOWO; AGUS NURYANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Raufanda MS, Prabowo RE, Nuryanto A. 2024. DNA barcoding of intertidal barnacles as potential bioindicators of microplastic pollution in Seribu Islands and Jakarta Bay, Indonesia. Biodiversitas 25: 4664-4676. Barnacles, with their sessile nature and filter-feeding behavior, hold significant potential as bioindicators of microplastic pollution. Due to the diverse morphotypes across barnacle species, DNA barcoding is a reliable technique for accurate taxonomic identification. This research aimed to determine intertidal barnacle species and identify potential bioindicators of microplastic pollution in Seribu Islands and Jakarta Bay, Indonesia. Barnacle samples were collected from seven locations using purposive sampling. Microplastic characteristics were analyzed visually and polymer-type testing was performed using Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR). Data was analyzed using Pearson correlation and bioconcentration factors to determine potential microplastic bioindicator species based on three criteria. The significance level was set at p<0.05 and all statistical analyses were performed using SPSS. Four species of intertidal barnacles were identified in Seribu Islands and Jakarta Bay, namely Amphibalanus amphitrite, Striatobalanus amaryllis, Amphibalanus zhujiangensis, and Newmanella radiata. DNA barcoding was used to determine the first three species, while morphological analysis identified the fourth species. The microplastic particle count varied among the species, with A. amphitrite showing the highest concentration at 42-53 particles/g. Due to its clear taxonomy, ease of surveying, and wide distribution, A. amphitrite has strong potential as a bioindicator of microplastic pollution, as it can accumulate more than other species.